Analisis buku ajar fisika kelas XI berdasarkan kategori pendekatan sains teknologi masyarakat - Yolly Sawitri; Yuri Yanti; Rahmi Laila; Yonira Mike; Festiyed Festiyed; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2019)
Changes in the industrial revolution 4.0 is a contextual aspect that is happening right now is a rapid change due to the discovery of new technologies. The changes are not only linear, but exponential. The impact is not only improving and improving, but it changes fundamentally which makes shifts in many aspects of life. These three STM components are related to each other. Science, Technology, and Society (STM) is an interdisciplinary field of study that seeks to explore and understand the many ways that modern science and technology shape modern culture, values, and institutions, on the one hand, and how modern values form science and technology. The existence of integration in the curriculum makes learning materials close to real-world situations. Thus, this integration is relevant to science because the natural essence found in the real world is an integrated pattern. Various problems are offered a solution by applying and using Multistrategic community technology. STM approach is an Indonesian translation of STS where this approach was first developed in the United States in the 1980s, and subsequently developed in the United Kingdom and Australia. Research objectives are needed for the final results to be achieved in research. Based on the background description, it can be stated the purpose of the study to be more directed. The purpose of this research is to analyze physics textbooks in class XI term 1 based on categories using Science, Technology and Society.Based on the results of analysis of Class XI Physics textbooks with the STM approach it can be concluded that 1) The aspects of science have a more dominant value compared to the aspects of technology and society; 2) Appropriate textbooks (“very good” category) with the STM approach are class XI Physics books for SMA / MA Class XI Curriculum 2013 Revised 2016